Perception of teachers on the challenges of school management in Ondo State, Nigeria (2025)
This study examined the perception of teachers on the challenges faced by school management. The study adopted a descriptive survey research design. The population of the study comprised teachers of public secondary schools in Akure North Local Government Area of Ondo State. The data used for the research was generated from six secondary schools in which 120 teachers were drawn randomly from the schools. The instrument used was the Teacher's Perception on the Challenges of School Management Questionnaire. Analysis was done using frequency count, percentage, and histogram. The outcomes show that poor teacher remuneration is the most prominent challenge from the teacher’s perspective. Finding a solution to the research outcome through school management, collaboration with government agencies and teamwork is the main solution to the challenges of school management. Based on the research outcomes, it was deduced that poor remuneration is the most prominent teachers ’perspective The recommendation was that the school administrators should solve the problems faced in the area of human and material resources. Besides, the government at all levels and non-governmental organizations are strongly encouraged to make funds available for the smooth running of the school.